Syncope and Oropharyngeal Malignancy – An Unusual Presentation - Megha Madhu; Vadisha Bhat; Shubha P. Bhat (Journal of Head & Neck Physicians and Surgeons)
Head-and-neck malignancies have varied presentations with oral, nasal, and otological symptoms. Rarely does a malignancy present with syncope. We report a case of a head-and-neck malignancy presenting with syncope, posing diagnostic dilemmas in the initial stages.